Efforts to Improve the Curiosity of Early Childhood Education Students by Implementing an Inquiry Approach at RA Al-Ma'soem - Marni (MANDAILING GLOBAL EDUKASIA, 2025)
This study aimed to improve the curiosity of early childhood education students through the implementation of an inquiry-based learning approach at RA Al-Ma'soem. Curiosity is an essential foundation for children’s cognitive development and active learning, yet classroom observations revealed that many students showed low enthusiasm in asking questions, exploring learning materials, and responding critically to teacher stimulation. This research employed Classroom Action Research (CAR) consisting of two cycles, each including the stages of planning, action, observation, and reflection. The participants were 20 students of early childhood education (aged 5–6 years) at RA Al-Ma'soem. Data were collected through observation sheets, teacher field notes, and documentation. The main indicator of success was the percentage of students demonstrating curiosity behaviors, including asking questions, exploring objects, expressing opinions, and responding to learning challenges. The findings showed a significant improvement in students’ curiosity after applying the inquiry approach. In the pre-cycle stage, the average curiosity achievement was 45% (low category). After the implementation in Cycle I, the curiosity level increased to 65% (moderate category). Furthermore, in Cycle II, the curiosity achievement reached 85% (high category), indicating that most students actively engaged in inquiry activities such as observing, questioning, experimenting, and communicating findings. The inquiry approach also increased students’ participation, confidence, and motivation during Islamic learning activities. Therefore, it can be concluded that the inquiry approach is effective in enhancing curiosity among early childhood learners and can be recommended as an innovative learning strategy in Islamic early childhood education institutions.